THE EFFECT OF USING SHORT STORY TOWARDS STUDENTS’ READING COMPREHENSION AT SECOND GRADE JUNIOR HIGH SCHOOL 3 PINTU GOBANG KARI - Husna, Ilma Sri Rozi Asma; Yusrida, Yusrida (Journal of English and Arabic Language Teaching, 2025)
This study aims to investigate the effect of using short stories on the reading comprehension of eighth-grade students at Junior High School 3 Pintu Gobang Kari. The research was motivated by students' low reading interest and limited reading comprehension skills in English texts. The method used was a pre-experimental design with a one-group pre-test and post-test design. The sample consisted of 22 students from class VIII-1 selected through purposive sampling. Data were collected through reading comprehension tests administered before and after the short story-based treatment. The results showed a significant improvement in post-test scores after the treatment. This was supported by a significance value (Sig. 2-tailed) of 0.032 < 0.05. Therefore, it can be concluded that the use of short stories has a significant positive effect on students’ reading comprehension. Short stories are proven to be an effecttive and enjoyable medium for enhancing students’ reading comprehension.